2016
DOI: 10.1590/1809-98232016019.150022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mat Pilates method on postural balance and thoracic hyperkyphosis among elderly women: a randomized controlled trial

Abstract: Objective: To evaluate the influence of the Mat Pilates method on thoracic hyperkyphosis and postural balance among elderly women. Method: A randomized longitudinal study was performed involving 31 elderly women who were divided into two groups: the Control Group (n=17) and the Pilates Group (n=14). The Pilates Group underwent training while the Control Group attended lectures. Evaluation consisted of specific balance (one-leg right and left) and thoracic kyphosis (computed biophotogrammetry) tests. The subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…On the other hand, the intervention may not have been vigorous enough to have an effect. Navega et al (2016) 30 found no effect on the static balance of the elderly after Pilates practice. Like Gabizon 29 , he argues that in order to improve balance, specific exercises should be included for this variable and he believes that assigning the improvement of the balance to an indirect increase in muscular strength is to overestimate the results.…”
Section: Balancementioning
confidence: 88%
“…On the other hand, the intervention may not have been vigorous enough to have an effect. Navega et al (2016) 30 found no effect on the static balance of the elderly after Pilates practice. Like Gabizon 29 , he argues that in order to improve balance, specific exercises should be included for this variable and he believes that assigning the improvement of the balance to an indirect increase in muscular strength is to overestimate the results.…”
Section: Balancementioning
confidence: 88%
“…In this condition, the COM is transferred forward, a change in the natural function of proprioception; muscle spindles; articular mechanical receptors, and weakness in the endurance and strength of back muscles. Such conditions lead to a postural control disorder, that was previously documented by Navega et al [13] and Jang et al [14].…”
Section: Introductionmentioning
confidence: 67%
“…Analyzing the benefit of the results observed and its repercussions from another evaluation point of view, the emphasis is that the reduction in shoulder angles can reflect a proposal of prevention and mitigation of the consequences of another problem associated with the aging process, which is the increase in the curvature of the dorsal region, usually accompanied by the abduction of the pectoral girdle, characterizing the thoracic kyphosis, a typical third-age posture change 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, positive effects may be produced on the flexibility 21,26 , factor that has direct influence on the posture pattern 26 , studies indicate that the PM can be used for optimization of quality of life 24,25 and may be an option of collective work, conducted in groups in the communities, since it does not require specialized environments or equipment, is easy to be implemented and has no additional costs to health teams as well as demand for qualified health professionals. This could represent an important contribution concerning the expansion of the range of body practices in collective health.…”
Section: Discussionmentioning
confidence: 99%